Need for relatedness: a self-determination approach to examining attachment styles, Facebook use, and psychological well-being. Issue 2 (3rd March 2016) - Lin, Jih-Hsuan
ABSTRACT: Employing attachment theory and self-determination theory, this study argues that attachment style represents essential innate needs for social connection among individuals and an important antecedent factor in social media research. Thus, attachment style influences how individuals use Facebook for social interaction to satisfy their need for relatedness and achieve psychological well-being. The results from university and national samples showed that individuals with high secure attachment gain satisfaction of the need for relatedness and perceive positive well-being, individuals with high attachment avoidance do not use Facebook for need satisfaction and perceive negative well-being, and individuals with high anxious attachment gain a sense of community through Facebook but still perceive loneliness. Indirect analyses showed that individuals with high secure and anxious attachment dimension lead to higher Facebook use, which provides a higher level of satisfaction of relatedness needs and results in more positive psychological outcomes. Additionally, communication with good friends on both Facebook and offline predicted higher well-being. These results successfully linked attachment theory to the self-determination process and extended both theories into the realm of social media. This study also provided a theoretical framework for future studies to examine the association between Facebook use and well-being. After controlling for personality traits including extraversion and self-esteem, attachment style still had considerable influence on psychological well-being, showing that attachment style is a distinct factor in predicting variances in well-being and further showing that innate need for relatedness is important when studying the need satisfaction process in social media. Future directions are discussed.